Longitudinal assessment of neuroimaging and clinical markers in autosomal dominant Alzheimer's disease: a prospective cohort study. Issue 8 (August 2015) - Yau, Wai-Ying Wendy; Tudorascu, Dana L; McDade, Eric M; Ikonomovic, Snezana; James, Jeffrey A; Minhas, Davneet; Mowrey, Wenzhu; Sheu, Lei K; Snitz, Beth E; Weissfeld, Lisa; Gianaros, Peter J; Aizenstein, Howard J; et al.
Summary Background The biomarker model of Alzheimer's disease postulates a dynamic sequence of amyloidosis, neurodegeneration, and cognitive decline as an individual progresses from preclinical Alzheimer's disease to dementia. Despite supportive evidence from cross-sectional studies, verification with long-term within-individual data is needed. Methods For this prospective cohort study, carriers of autosomal dominant Alzheimer's disease mutations (aged ≥21 years) were recruited from across the USA through referrals by physicians or from affected families. People with mutations in PSEN1, PSEN2, or APP were assessed at the University of Pittsburgh Alzheimer's Disease Research Center every 1–2 years, between March 23, 2003, and Aug 1, 2014. We measured global cerebral amyloid β (Aβ) load using 11C-Pittsburgh Compound-B PET, posterior cortical metabolism with 18F-fluorodeoxyglucose PET, hippocampal volume (age and sex corrected) with T1-weighted MRI, verbal memory with the ten-item Consortium to Establish a Registry for Alzheimer's Disease Word List Learning Delayed Recall Test, and general cognition with the Mini Mental State Examination. We estimated overall biomarker trajectories across estimated years from symptom onset using linear mixed models, and compared these estimates with cross-sectional data from cognitively normal control individuals (age 65–89 years) who were negative for amyloidosis, hypometabolism, and hippocampal atrophy. In the mutation carriers who had the longest follow-up, we examined the within-individual progression of amyloidosis, metabolism, hippocampal volume, and cognition to identify progressive within-individual changes (a significant change was defined as an increase or decrease of more than two Z scores standardised to controls). Findings 16 people with mutations in PSEN1, PSEN2, or APP, aged 28–56 years, completed between two and eight assessments (a total of 83 assessments) over 2–11 years. Significant differences in mutation carriers compared with controls (p<0·01) were detected in the following order: increased amyloidosis (7·5 years before expected onset), decreased metabolism (at time of expected onset), decreased hippocampal volume and verbal memory (7·5 years after expected onset), and decreased general cognition (10 years after expected onset). Among the seven participants with longest follow-up (seven or eight assessments spanning 6–11 years), three individuals had active amyloidosis without progressive neurodegeneration or cognitive decline, two amyloid-positive individuals showed progressive neurodegeneration and cognitive decline without further progressive amyloidosis, and two amyloid-positive individuals showed neither active amyloidosis nor progressive neurodegeneration or cognitive decline. Interpretation Our results support amyloidosis as the earliest component of the biomarker model in autosomal dominant Alzheimer's disease. Our within-individual examination suggests three sequential phases in the development of autosomal dominant Alzheimer's disease—active amyloidosis, a stable amyloid-positive period, and progressive neurodegeneration and cognitive decline—indicating that Aβ accumulation is largely complete before progressive neurodegeneration and cognitive decline occur. These findings offer supportive evidence for efforts to target early Aβ deposition for secondary prevention in individuals with autosomal dominant Alzheimer's disease. Funding National Institutes of Health and Howard Hughes Medical Institute.